(untitled) (Revista Brasileira de Contabilidade e Gestão, 2023)
The present study aimed to analyze the networks with a focus on innovation that arise as a new form of work organization and interaction between organizations. The nets were identified by means of a mapping done on the internet. In Brazil it was noted the existence of 30 networks and of these, 09 are of innovation. The Southeast region is distinguished by the number of networks with (04). In short the networks have similar purposes. The interaction between local entrepreneurs, creating culture toward the importance of innovation and the strengthening of graduate programs generate economic sustainability and consequently the strengthening of associates.